On The Margins of Language: Ideophones, Interjections and Dependencies in Linguistic Theory - Dingemanse, Mark (My University, 2017)
On the margins of language: Ideophones, interjections and dependencies in linguistic theory.
Keywords: Ideophones; Interjections; linguistic theory